Fighting fit the SAS fitness guide - Weale, Adrian
Every year thousands of men and women discover new levels of fitness and inner strength as they are put through their paces to meet demanding standards required for new recruits in the British Army - this book will take you to the same level. Beyond that are the elite: the SAS, Paras and Commandos. Each unit has rigorous and searching requirements designed to select only the strongest, fittest and meanest for the world's toughest regiments. Recommended by a recent SAS squadron commander as 'an excellent guide', FIGHTING FIT's unique and proven training programmes have already helped many soldiers pass these most demanding tests. Now you can join them. Illustrated throughout and including inside information on the kit you'll need, the food you should eat and how to cope with injury, FIGHTING FIT is the comprehensive insider's guide to the fitness methods of the world's most professional army.